PENGARUH AKTIVA PAJAK TANGGUHAN DAN BEBAN PAJAK TANGGUHAN TERHADAP MANAJEMEN LABA - Hakim, Arif Rachmad; Praptoyo, Sugeng (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
This research is meant to find out the influence of deferred tax assets and deferred tax expense on earnings management to the banking companies which are listed in Indonesia Stock Exchange during the 2011-2013 periods. The research method is quantitative research methods. The data is secondary data which has been obtained through intermediary medium that has been processed and documented. The samples have been selected by using purposive sampling method. In order to test the hypothesis, this study is done by using the multiple linear regressions analysis. Based on the results of multiple linear regression analysis with the significance level of 10%, this research shows that: deferred tax assets and deferred tax expense has significant influence to the earnings management.Keywords: Deferred Tax Assets, Deferred Tax Expense, and earnings management.